AN ANALYSIS OF COMMISSIVE SPEECH ACT USED BY THE MAIN CHARACTER OF “KNIVES OUT” - Maya Fitriana Devi; Agwin Degaf (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Commissive speech acts are speech acts that bind the speaker to carry out what is stated in the speech. This research aims to analyze the types and the functions of commisives speech acts used by the characters in the Knives Out movie. The method used in this research is qualitative descriptive in which the research instrument is the researcher herself. The utterances were classified based on the theory proposed by Searle (1985) and Austin (1969). The utterances found in that movie are classified into six types of commisives speech act: the promise, guarantee, refusal, threat, volunteer, and offer. The results revealed there are 13 data found in the Knives Out film. The function that the characters mainly use in the film is an act of illocution. In contrast, from 13 data, the researcher found 6 types of commisive speech acts are found in the Knives Out movie: 2 utterances for guarantee (guarantee), 2 utterances for promises (promise), 2 utterances for offers (to offer), 3 utterances for refuse (refuse), 2 utterances for threats (threatening), and 2 utterances for volunteers (volunteers). Then, the commissive speech act that is mainly produced by the characters is rejection.